Characteristics and Management of Children With COVID-19 in a Tertiary Care Hospital in Turkey. (March 2021) - Yayla, Burcu Ceylan Cura; Aykac, Kubra; Ozsurekci, Yasemin; Ceyhan, Mehmet
Introduction: Limited data are available for pediatric patients with coronavirus disease 2019 (COVID-19), especially with regard to disease management strategies. Objective: To assess the children with COVID-19. Method: We conducted a retrospective review of the medical records of pediatric patients on March 11 and May 23, 2020. Results: We evaluated 77 COVID-19 pediatric patients, of whom 45.5% were male, with a median age of 8 years (interquartile range [IQR] = 2-13), and 6.4% had underlying diseases. Patients were classified according to severity, with the percentages of asymptomatic, mild, moderate, and critical/severe cases determined to be 24.7%, 41.6%, 29.9%, and 3.9%, respectively. Extracorporeal membrane oxygenation and mechanic ventilation were only required for 1 patient. Targeted therapies were used in 3 patients. Conclusion: The disease course of COVID-19 appears to be milder in children than in adults, and the treatment course primarily consists of supportive care.